Functional Capacity and Motor Performance of Upper Limbs in Individuals with Cerebellar Disorders: A Pilot Study - Vivian Farahte Giangiardi; Sandra Maria Sbeghen F. de Freitas; Flávia P. de Paiva Silva; Renata Morales Banjai; Sandra Regina Alouche (Behavioural Neurology)
In simple daily activities carried out by the upper limbs, the cerebellum is responsible for the adaptations required for the accurate movement based on previous experiences and external references. This paper aims to characterize the performance of the upper limbs after a cerebellar disease. We evaluated the digital and handgrip strength, dexterity, and function of the upper limbs. The motor performance of the upper limbs was assessed through the use of a digitizing tablet by performing aiming movements with the upper limb most affected by cerebellar disease and the paired limb of the healthy group. The results showed differences between groups: the cerebellar group had higher latency to movement onset, was slower, and presented less smooth trajectories and higher initial direction errors. Moreover, the movement direction influenced the peak velocity and the smoothness for both groups (contralateral directions were slower and less smooth). We concluded that cerebellar disorder leads to movement planning impairment compromising the formulation of an internal model. Alterations on movement execution seem to be a consequence from disruptions in the anticipatory model, leading to more adaptations. These findings are compatible with the roles of the cerebellum on the control of voluntary movement.